ORAL AGREEMENT: LEGAL FORCE AND VALIDITY UNDER THE CIVIL CODE - Dewa Ayu Ari Dwi Karina Subandi; I Wayan Novy Purwanto (Transpublika Publisher, 2024)
The objective of this research is to examine legal validity of oral agreements based on the Civil Code and to recognize as well as understand the validity of oral agreements according to the Civil Code. The legal research method employed is normative research, with an approach to legislation and conceptual approach. Additionally, the legal materials are sourced from secondary legal materials and primary legal materials. The primary source is the Civil Code, while the secondary source includes books and scientific journals. The findings of this study indicate that, in accordance with the Civil Code, oral agreements possess legal validity. This legal validity is applicable to the parties involved in their creation. The legal validity involves a mutual obligation. The obligation is to willingly bind oneself and together in the oral agreement. The legal validity of oral agreements is closely linked to the validity of an agreement being deemed to have legal validity or meeting the requirements for its validity. An oral agreement is considered a valid agreement if it encompasses both of these elements.